2016
DOI: 10.5194/esurf-4-685-2016
|View full text |Cite
|
Sign up to set email alerts
|

Gravel threshold of motion: a state function of sediment transport disequilibrium?

Abstract: Abstract. In most sediment transport models, a threshold variable dictates the shear stress at which nonnegligible bedload transport begins. Previous work has demonstrated that nondimensional transport thresholds (τ * c ) vary with many factors related not only to grain size and shape, but also with characteristics of the local bed surface and sediment transport rate (q s ). I propose a new model in which q s -dependent τ * c , notated as τ * c(q s ) , evolves as a power-law function of net erosion or depositi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 72 publications
2
58
0
Order By: Relevance
“…Downstream from the dam site, river response to a pulse of reservoir sediment is commonly anticipated to include aggradation, channel widening, filling of riverbed pools, and bed‐sediment fining (Cui et al, ; Downs et al, ; Pizzuto, ), changes generally confirmed by field studies to date (e.g., Major et al, ; Pearson et al, ; Tullos et al, ; Wang & Kuo, ; Wilcox et al, ; Wohl & Cenderelli, ). These geomorphic responses to newly introduced sediment supply might be expected to change the river corridor's sensitivity to discharge, given that aggradation generally increases channel‐floodplain connectivity and that smoothing of bed topography by new deposition can enhance sediment mobility (Johnson, ; Venditti et al, ). However, because few large dams (>10 m tall) have been removed thus far, relatively little is known about the detailed sedimentary and geomorphic response over substantial spatial or temporal scales following a large dam‐removal sediment release (Major et al, ), including subsequent response to flow forcing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream from the dam site, river response to a pulse of reservoir sediment is commonly anticipated to include aggradation, channel widening, filling of riverbed pools, and bed‐sediment fining (Cui et al, ; Downs et al, ; Pizzuto, ), changes generally confirmed by field studies to date (e.g., Major et al, ; Pearson et al, ; Tullos et al, ; Wang & Kuo, ; Wilcox et al, ; Wohl & Cenderelli, ). These geomorphic responses to newly introduced sediment supply might be expected to change the river corridor's sensitivity to discharge, given that aggradation generally increases channel‐floodplain connectivity and that smoothing of bed topography by new deposition can enhance sediment mobility (Johnson, ; Venditti et al, ). However, because few large dams (>10 m tall) have been removed thus far, relatively little is known about the detailed sedimentary and geomorphic response over substantial spatial or temporal scales following a large dam‐removal sediment release (Major et al, ), including subsequent response to flow forcing.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis originates from previous observations of stream responses to increased sediment supply, including aggradation, bed instability, and planform alterations, and follows from the premise that newly introduced sediment supply both aggrades the riverbed, allowing flow to spread readily into the floodplain, and, being commonly finer than the preexisting bed, requires lower shear stress to remobilize the newly deposited bed material (e.g., Ashworth et al, ; Hoffman & Gabet, ; Mohrig et al, ; Recking et al, ; Schumm, ; N. D. Smith & Smith, ). As mentioned above, smoothing of bed topography as sediment pulses fill riverbed pools may also result in more efficient sediment transport (Johnson, ), potentially shaping a channel in which greater topographic change occurs for a given discharge during and in the waning phase of a sediment pulse compared to the relatively sediment‐starved condition prior to the pulse. Thus, we reevaluate the concept of threshold stream power necessary to cause geomorphic change, focusing on the potential contributing factor of sediment supply.…”
Section: Introductionmentioning
confidence: 99%
“…SPACE does not contain independent descriptions of the roughness of bedrock and sediment, and does not distinguish between the case in which bedrock is rougher than sediment and the one in which sediment is rougher than bedrock (e.g., Inoue et al, 2014;Johnson, 2014). We also do not model the potential driving of bedrock erosion by bed load sediment (the tools effect), as used by Sklar and Dietrich (2004), Chatanantavet and Parker (2009), Turowski (2009), Inoue et al (2014, 2016, Zhang et al (2015), and other saltation-abrasion-type models. Both width dynamics and bed load abrasion could be incorporated without changing the underlying model structure but have been omitted in order to facilitate numerical model comparison to analytical solutions.…”
Section: The Space Modelmentioning
confidence: 99%
“…Using a distribution of entrainment thresholds helps to account for the observation that incipient sediment motion does not begin at the same threshold value for all particles (e.g., Buffington and Montgomery, 1997). Variability in the threshold for motion is thought to be a function of grain size and shape variations (Kirchner et al, 1990;Wilcock and McArdell, 1997;Prancevic and Lamb, 2015), grain hiding and protrusion effects (Kirchner et al, 1990;Parker, 1990;Wilcock and McArdell, 1997;McEwan and Heald, 2001), bed sorting (Nelson et al, 2009), sediment flux (Johnson, 2016), and flow history (Masteller and Finnegan, 2017). Similarly, the threshold for bedrock erosion can depend on subreach-scale mineralogy, joint spacing and orientation, and the weathered state of the bedrock.…”
Section: Optional Smoothing Of Entrainment/erosion Thresholdsmentioning
confidence: 99%
“…This approach was not possible for the experiments, as the clear water depth was highly variable 10 and not measurable due to the shallow flow over the changing sediment deposits. As an alternative, a relationship for the equilibrium slope was applied, as proposed by (Johnson, 2016): …”
Section: Sediment Depositionmentioning
confidence: 99%